2015
DOI: 10.1002/ppul.23155
|View full text |Cite
|
Sign up to set email alerts
|

Transition of respiratory technology dependent patients from pediatric to adult pulmonology care

Abstract: The survey results highlight a lack of standardized transition programs at US children's hospitals for the transfer of RTD patients from a pediatric to an adult care setting. Improvement in the standardized management of transitions of complex RTD patients from pediatric to adult care may decrease the risk for adverse health outcomes and the stresses associated with changing the health care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Therefore, some study patients may have transitioned out before 21 years of age and were not appropriately censored. Given that older complex patients frequently use pediatric services and few pediatric home ventilation programs have formalized transition processes, we felt that an upper age limit of 21 years was reasonable . Fifth, we did not have access to some information that are worthy of study, namely reasons for (and reasons for not) transitioning to transtracheal ventilation and causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some study patients may have transitioned out before 21 years of age and were not appropriately censored. Given that older complex patients frequently use pediatric services and few pediatric home ventilation programs have formalized transition processes, we felt that an upper age limit of 21 years was reasonable . Fifth, we did not have access to some information that are worthy of study, namely reasons for (and reasons for not) transitioning to transtracheal ventilation and causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…There is a constant challenge to address the primary care needs of these individuals, as adults. Standardized transition programs are needed to improve patient satisfaction [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…A survey of pediatric pulmonology programs found that most did not utilize a standard transition process for ventilator-dependent patients, and many did not have a process in place. 31 Unlike the consensus report for cystic fibrosis adult care, 17 there are no published guidelines addressing transition of ventilator-dependent patients from pediatric to adult care. 32 Although a consensus statement exists for transition of children with special health care needs, 5 different chronic conditions bring unique disease-specific considerations that must be taken into account.…”
Section: Condition-specific Models Of Transitionmentioning
confidence: 99%